Market size and foreign direct investment in sub-Saharan Africa: the role of education - JEMILUYI Olofunmilayo Olayemi; DADA James Temitope (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study examines the role of education in the nexus between foreign direct investment (FDI) and market size in sub-Saharan African countries from 2005 to 2015 using a panel of 30 countries. Market size is proxy by gross domestic product and population while two variables are used to measure education; primary school enrolment and secondary school enrolment. Difference Generalised Method of Moments (GMM) is used as the estimation technique. The result shows that education and market size have positive and significant effect on foreign direct investment. The interactive effect of market size (population and gross domestic product) and education (both primary and secondary school enrolment) has positive effect on foreign direct investment. The study concludes that policy maker in the region should focus more on the quality of education rather than quantity of education.